INTEGRATION OF ASWAJA VALUES IN ENHANCING THE MODERATION OF THE NURUL JADID ISLAMIC BOARDING SCHOOL - Hakimah, Hakimah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
With many different races, ethnicities, cultures, and faiths, Indonesia is a pluralistic nation. As character characterises moderation, steps to combat radicalism and theorizing with religious undertones are all being strengthened. This distinction deserves its own discussion in the field of education. The study of Islamic religious education in public schools based on Islamic boarding schools is extremely fascinating to debate at this time, Islamic boarding schools do not only study religious knowledge but also general science. This study employs a qualitative methodology. Data were gathered using participant observation, interviews, and related documentation. From these data the researcher or orgaorganised model based on the values of aswaja in the Islamic boarding school, including: the attiattitude of asut, tawazun, I'tidal, tasamuh, musawah, shura, islah, Awaliyah, tatawur wa ibtikar, and tahadIftikhar the hbahadur curriculum development, it is also able to present a moderate Islamic movement among Islamic boarding schools which teaches to build tolerance among people, accept the opinions of others, and so on. Research recommends the importance of teaching practising ng religpractisingation in Islamic boarding schools in order to be able to present a moderate and moral Islamic movement